ISSLEDOVANIE EFFEKTIVNOSTII BEZOPASNOSTI TERAPII TERIPARATIDOM(FORSTEO) V TEChENIE 1 GODA PRI POSTMENOPAUZAL'NOMOSTEOPOROZE - L Ya ROZhINSKAYa; S D ARAPOVA; L K DZERANOVA; N N MOLITVOSLOVOVA; A V IL'IN; N I SAZONOVA; T O ChERNOVA; A A ShIShKINA; I I DEDOV; L I BENEVOLENSKAYa; O A NIKITINSKAYa; T A KOROTKOVA; et al. (Остеопороз и остеопатии, 2006)
The aims of the reported multinational open study were to estimate the influence of subcutaneous injections of 20 mkg daily Teriparatide on bone mineral density (BMD) at the lumbar spine and proximal femur, the markers of bone metabolism, the quality of life as well as the safety of treatment. Duration of the treatment period was one year. Fifty postmenopausal women with osteoporosis (L1-L4 T-score mean -3,2±0,6 SD) were enrolled in the study. 70,8% of patients had fragility fractures. Forty four patients (78%) remained until the end of the study. BMD was detected by dual energy X-ray absorptiometry (DXA) («Prodigy», Lunar and «Hologic» 4500 W) at the lumbar spine (L1-L4) and proximal femur with converting to the standardized BMD. Bone alkaline phosphatase (BAP) and osteocalcin (OC) were measured as markers of bone formation and C-terminal cross-linking telopeptide (CTX) were measured in serum as a marker of bone resorption. The significant increase in BMD was found at the lumbar spine (L1-L412,5±6,6%), whereas BMD at the proximal femur did not change significantly. The levels of markers of bone metabolism were increased after 3 months of the treatment and to the end of the study were 192,2%; 385%; 526,3% higher versus the baseline levels for BAP, OC., CTX consequently. There was also found a significant improvement in the quality of life of the patients which was estimated by EQ-5D inquirer at the baseline visit and at the end of the study. The adverse effects, which were related to the teriparatide injections, were observed in 44% of the patients. Due to the adverse effects Tereiparatide was cancelled for 6 (12%) patients. In other cases the adverse effects were slight and the cancellation of treatment was not required. Conclusions: The daily injections of Teriparatide (20 mkg) during 1 year provide the significant increase in BMD at the lumbar spine for postmenopausal women with osteoporosis as well as the early increase in the bone turnover rate. Treatment with Teriparatide improves the quality of life for women with postmenopausal osteoporosis. The daily injections of Teriparatide during 1 year are well tolerated and safe.